High genetic similarity between non-typhoidal Salmonella isolated from paired blood and stool samples of children in the Democratic Republic of the Congo. - Marie-France Phoba; Barbara Barbé; Benedikt Ley; Sandra Van Puyvelde; Annelies Post; Wesley Mattheus; Stijn Deborggraeve; Octavie Lunguya; Jan Jacobs (Public Library of Science (PLoS), 2020)
BACKGROUND:Non-typhoidal Salmonella (NTS) serotypes Typhimurium and Enteritidis are a major cause of bloodstream infections in children in sub-Saharan Africa but their reservoir is unknown. We compared pairs of NTS blood and stool isolates (with the same NTS serotype recovered in the same patient) for genetic similarity. METHODS:Between November 2013 and April 2017, hospital-admitted children (29 days to 14 years) with culture-confirmed NTS bloodstream infections were enrolled in a cross-sectional study at Kisantu Hospital, DR Congo. Stool cultures for Salmonella were performed on a subset of enrolled children, as well as on a control group of non-febrile hospital-admitted children. Pairs of blood and stool NTS isolates were assessed for genetic similarity by multiple-locus variable-number of tandem repeats (MLVA) and genomics analysis. RESULTS:A total of 299 children with NTS grown from blood cultures (Typhimurium 68.6%, Enteritidis 30.4%, other NTS 1.0%) had a stool sample processed; in 105 (35.1%) of them NTS was detected (Typhimurium 70.5%, Enteritidis 25.7%, other NTS 3.8%). A total of 87/105 (82.9%) pairs of blood and stool NTS isolates were observed (representing 29.1% of the 299 children). Among 1598 controls, the proportion of NTS stool excretion was 2.1% (p < 0.0001). MLVA types among paired isolates were identical in 82/87 (94.3%) pairs (27.4% of the 299 children; 61/66 (92.4%) in Typhimurium and 21/21 (100%) in Enteritidis pairs). Genomics analysis confirmed high genetic similarity within 41/43 (95.3%) pairs, showing a median SNP difference of 1 (range 0-77) and 1 (range 0-4) for Typhimurium and Enteritidis pairs respectively. Typhimurium and Enteritidis isolates belonged to sequence types ST313 lineage II and ST11 respectively. CONCLUSION:Nearly 30% of children with NTS bloodstream infection showed stool excretion of an NTS isolate with high genetic similarity, adding to the evidence of humans as a potential reservoir for NTS.